EGR3 Immediate Early Gene and the Brain-Derived Neurotrophic Factor in Bipolar Disorder - Pfaffenseller, Bianca; Kapczinski, Flavio; Gallitano, Amelia L.; Klamt, Fábio (Frontiers in Behavioral Neuroscience, 2018)
Bipolar disorder (BD) is a severe mental illness with a strong genetic component, involving complex interactions between numerous genes and environmental factors. Immediate early genes (IEGs) are activated in the brain in response to environmental stimuli, such as stress. The potential to translate environmental stimuli into long-term changes in brain has led to increased interest in a potential role for these genes influencing risk for psychiatric disorders. Our recent finding using network-based approach has shown that the regulatory unit of early growth response gene 3 (EGR3) of IEGs family was robustly repressed in postmortem prefrontal cortex of BD patients. As a central transcription factor, EGR3 regulates an array of target genes that mediate critical neurobiological processes such as synaptic plasticity, memory and cognition. Considering that EGR3 expression is induced by brain-derived neurotrophic factor (BDNF) that has been consistently implicated in BD pathophysiology, we suggest a link between BDNF and EGR3 and their potential role in BD. A growing body of data from our group and others has shown that peripheral BDNF levels are decreased during mood episodes and also with illness progression. In this same vein, BDNF has been proposed as an important growth factor in the reduced cellular resilience related to BD. Taken together with the fact that EGR3 regulates the expression of the neurotrophin receptor p75NTR and may also indirectly induce BDNF expression, here we propose a feed-forward gene regulatory network involving EGR3 and BDNF and its potential role in BD.